2017
DOI: 10.1103/physrevapplied.8.064025
|View full text |Cite
|
Sign up to set email alerts
|

Thermalization, Freeze-out, and Noise: Deciphering Experimental Quantum Annealers

Abstract: By contrasting the performance of two quantum annealers operating at different temperatures, we address recent questions related to the role of temperature in these devices and their function as 'Boltzmann samplers'. Using a method to reliably calculate the degeneracies of the energy levels of large-scale spin-glass instances, we are able to estimate the instance-dependent effective temperature from the output of annealing runs. Our results corroborate the 'freeze-out' picture which posits two regimes, one in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 31 publications
4
59
0
Order By: Relevance
“…The specific spin system we study, namely spin glasses, is very relevant as current experimental quantum annealers attempt to solve precisely this type of problem. With questions still lingering about which distribution these devices sample from [30], it is important to have an accurate tool to estimate the DOS (for instance to understand thermalization [30]). For this problem we specifically consider instances with vastly different hardnesses, confirming that the accuracy of the technique proposed degrades significantly less for harder samples that previous approaches.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The specific spin system we study, namely spin glasses, is very relevant as current experimental quantum annealers attempt to solve precisely this type of problem. With questions still lingering about which distribution these devices sample from [30], it is important to have an accurate tool to estimate the DOS (for instance to understand thermalization [30]). For this problem we specifically consider instances with vastly different hardnesses, confirming that the accuracy of the technique proposed degrades significantly less for harder samples that previous approaches.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…It follows then that the planted solution is also a ground state of the total Hamiltonian. This class of instances has two attractive properties: (i) the ground-state energies of the generated problems are known in advance, and (ii) the exact degeneracies of the ground and first excited states are computable [27,30]. These in turn allow us to check how close entropic samplers come to these exact values.…”
Section: Verifiable Benchmarking Of Entropic Samplersmentioning
confidence: 99%
See 2 more Smart Citations
“…To make matters worse, Ref. [13] found that effective sampling temperatures on an experimental quantum annealer tend to increase with problem size. Embedding therefore inevitably leads to the observation of states which are not in the logical subspace, and since the probability of this occurring nominally scales exponentially in N (Eq.…”
Section: Discussionmentioning
confidence: 99%